Proportional representation and incidence rate of repeat visits in ethnic minorities compared to native Dutch people under the age of 25 years in the Netherlands - Y.J. Evers; A. Verhaegh; A. Ibrahim; C. Peters; N.H.T.M. Dukers-Muijrers; R. Reijs; C.J.P.A. Hoebe (Journal of Migration and Health)
Introduction: Migration is a growing phenomenon and has impact on sexual and reproductive health outcomes, such as an increased burden for STIs, sexual violence and unintended pregnancies. Equitable access to sexual health care is of great importance for young people from ethnic minorities (EMs). In this study, we aimed to determine the proportional representation of first- and second generation EMs under 25 years at Dutch Sexual Health Centers (SHCs) compared to native Dutch citizens. Methods: In this retrospective cohort study, coded health records data of 270,927 persons in the age group of 15 till 24 years visiting SHCs between 2016 and 2021 were included. Health records data was combined with census tract data (Statistics Netherlands) to average annual calculate consultation rates, i.e., dividing 6-year-average of the number of first consultations of a patient in the study period belonging to a specific EM by the total number of citizens in the age group of 15 till 24 years belonging to that EM in the Netherlands in 2021, multiplied by 1000. Results: The consultation rate for native Dutch patients was 22.0 per 1000 persons (95 %CI: 21.8–22.2, 18.9, 19.8 (95 %CI: 19.8–20.4) for first-generation EMs and 18.4 (95 %CI: 18.0–18.8) for second-generation EMs. In both first- and second generation EMs, consultation rates for patients from Turkey, Morocco, Eastern Europe and Asia were lower than for native Dutch patients. Consultation rates among patients from Africa were lower for first-generation EMs than native Dutch patients. Consultation rates among patients from Indonesia, Suriname/Dutch Antilles, Latin America and other western countries were equal or higher than among native Dutch patients Discussion: Our study showed that several EMs were underserved in Dutch sexual health care, suggesting lower access to care and indicating the need for culturally sensitive approaches to increase access. Using consultation rates is informative to indicate inequalities in access to sexual health care among EMs.